Perceptions of Science Teachers from Marawi City High Schools on the Kto12 Curriculum Implementation - Said-Ador, Norolayn K. (International Journal of Learning, Teaching and Educational Research, 2016)
The Department of Education (DepEd) has an impetus for Kto12 Curriculum implementation. However, this remains an issue due to argument that it is merely a superficial solution. And it does not truly address the country’s more fundamental educational problems. Accordingly, the study was conducted during its second year implementation and it only included grade 7 and 8 science teachers to investigate their perceptions as well as to know the relationships of some variables pertaining to teachers’ characteristics and their type of school. Descriptive with correlational type of research method was employed. The study found out that many science teachers positively perceived on the curriculum implementation and agreed on its rationale, education vision and goals, and benefits stipulated by the DepEd. On the other hand, some had negative impression on the transition due to lack of readiness and discrepancy of reproduced learning materials for the teachers on classroom instruction. In addition, more science teachers from public high schools attended the Kto12 trainings and used the said materials than those from private high schools. Moreover, there was a significant relationship between the teachers’ attendance in the Kto12 trainings and their usage of materials in the classroom instruction. The study suggested that DepEd ought to send their teachers on Kto12 trainings to prepare them for the curriculum transition. Additionally, thorough examination on the Kto12 materials shall be conducted by DepEd to meet what it intends to implement and attain.